Teaching without learning? A problem in health sciences - Richard, Enrique (2024)
In Bolivia and Ecuador, there is a concept and interpretation of the teaching-learning process of a bivariate causal type of net behavioral nature  (PEAc). The problem arises when, based on this interpretation, institutional policies and regulations are developed that affect education, society and even the country. Said PEAc represses creativity, motivation and even violates human rights. In teachers and students, it represses the possibility of learning to think and developing fundamental metacognitive skills. The objective of this essay and review is to analyze the problem from the behavioral roots that gave rise to the questioned concept to demonstrate, from the logical, biological, psychopedagogical and epistemological point of view that the assumptions raised around said concept are fallacies, false enthymemes, cognitive biases and/or neuromyths that harm the normal performance of academic activities at all levels. It is essential for society to have creative citizens who know how to find new solutions to new or known problems, who develop research, arts and all forms of culture freely. It is proposed to motivate future university students to choose careers based on their vocation as a motivational factor that promotes their permeability to learning.